Surgical management of an inguinal hernia in a female dog: Case report - Reno Pinhotti, Nicole; Ribeiro Divan, Beatriz; Santos Ramos, Beatriz; Nocelli Nogueira, Gabriela; Gregório Morais, Rafaela; Simião Payão, Thaís; da Silva Pinto, Bruna; Meireles dos Reis, Fernanda; Elias Silva Biazzo, Leandro; Bitencourt Pascoal, Livia (Pubvet, 2024)
Inguinal hernia is a common condition in dogs, characterized by the protrusion of abdominal tissues through the abdominal wall in the inguinal region. It can be congenital or acquired, and is more frequent in unspayed females of small breeds. Its most characteristic clinical sign is the presence of a palpable mass in the inguinal region that may increase in size with physical force. The diagnosis is usually made through physical examination and can be confirmed by imaging studies, with the importance of differentiating it from mammary neoplasms which can also manifest in the region. Definitive treatment is surgical, involving the reduction of the hernia and closure of the opening in the abdominal wall. This report describes the case of a thirteen-year-old unspayed female Pinscher who was seen due to the presence of neoplasms in several mammary glands, including the inguinal, and a pedunculated vulvar neoformation. The patient was referred to the surgical department where it was found that, in addition to the mammary neoplasms, she had an inguinal hernia of approximately 7 centimeters in diameter, with protrusion of abdominal tissues. During the surgical procedure, it was identified that the spleen and uterus with pyometra were incarcerated in the inguinal hernia, necessitating the repositioning of the abdominal structures, an ovariohysterectomy and a herniorrhaphy. The patient recovered well, with a favorable prognosis, and mastectomy was recommended after 15 days. The prognosis for inguinal hernia is generally good with appropriate surgical intervention, but complications such as hernia strangulation require early diagnosis and treatment.